Phylogenetic relationships of Silene sections Lasiostemones and Sclerocalycine (Caryophyllaceae) in Iran - Bahmani, Fatemeh; Assadi, Mostafa; Yildiz, Kemal; Mehregan, Iraj (Phytotaxa, 2020)
A phylogenetic study of Silene sect. Lasiostemones and sect. Sclerocalycine in Iran is presented. A total of 72 accessions (43 of which obtained from GenBank) were analyzed using nuclear ITS and chloroplast rps16 markers. It was shown that sect. Lasiostemones is not a monophyletic group, including members which would belong to sect. Sclerocalycine (i.e. S. tenella, S. longipetala, S. lasiantha, S. marschallii, S. propinqua) and sect. Siphonomorpha (i.e. S. ghahremaninejadii, S. shahrudensis, S. saxatilis, S. ruprechtii, S. parrowiana).